Publiek Park : Wandelgids : Citadelpark 2021. - Declercq, Jef; van der Werf, Adriënne; Laganovska, Anna; Persyn, Koi; Jacobs, Maya; van Son, Annabelle; Cosyns, Marc; De Vos, Els; Lambrechts Cruz, Lisa; Luyten, Anna; Saelemakers, Samuel; Sterckx, Marjan; et al. ([S.l.] : Vrienden v/h S.M.A.K., 2021)
Ancãns, Kristaps ; Claus, Ines ; CMMC ; Cosyns, Marc ; De Meutter, Koba ; Dheedene, Stefaan ; Dudek, Marcin ; Flanagan, Helen Anna ; Grootes, Mark ; Kanis, Polina ; Leenhardt, Gaëlle ; Meirhaeghe, Benjamin Abel ; Miller, Quenton ; mountaincutters ; Ngoya, Anthony ; Nikvashvili, Shalva ; Pagin, Jacopo ; Prouvost, Laure ; Spilliaert, Clara ; Vasiljeva, Evita ; Wang, Xuan-Lin ; Weinberger, Lois
Publiek Park, curated by Jef Declercq, Anna Laganovska, Koi Persyn & Andriënne van der Werf, Citadelpark Gent, 01.07.2021 - 04-07-2021
boek